Group Portrait of the Galician Oil Entrepreneurs - Franaszek, Piotr (Studia Historiae Oeconomicae, 2022)
When presenting the careers of entrepreneurs operating on Polish soil at the turn of the 19th and 20th centuries, researchers usually focus on individuals operating in the most industrialised areas, especially the Kingdom of Poland. Much less attention has been paid to successful entrepreneurs in Galicia. Studies on Galician entrepreneurship have mainly taken the form of biographical entries in encyclopaedias and lexicons and in the Polish Biographical Dictionary. These are profiles of individual business leaders of the Austrian partition, while far fewer works deal with the issue of entrepreneurs as a group, despite the fact that there are many sources for such research. This article is an attempt to create a group portrait of a number of Galician oil entrepreneurs who played an exceptional role in the economic, the social, and the political life of Galicia.